2020
DOI: 10.1177/1461348420935665
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic characteristics of planetary gear transmission system considering squeeze oil film

Abstract: Based on the planetary gear transmission system considering the coupling effects of friction and elastohydrodynamic lubrication, a torsional dynamic model considering friction, oil film, time-varying meshing stiffness, meshing damping, and gear backlash is established. The Runge–Kutta numerical method is used to solve the vibration equation of the system. The bifurcation diagram and largest Lyapunov exponent are used to analyze the dynamic characteristics of the system under different bifurcation parameters su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…T c1 is the friction torque of the inner gear ring and the planetary frame, which is related to the pressure applied by the friction clutch, the number of friction plates and the friction coefficient of the friction plates, as shown in Eq. (6), where R o is the radius of the outer circle of the friction plate, and R i is the radius of the inner circle of the friction plate. T L (t) is the load torque applied on the output shaft of the driveline.…”
Section: A Mathematical Model Of a Two-speed Transmission System In H...mentioning
confidence: 99%
See 1 more Smart Citation
“…T c1 is the friction torque of the inner gear ring and the planetary frame, which is related to the pressure applied by the friction clutch, the number of friction plates and the friction coefficient of the friction plates, as shown in Eq. (6), where R o is the radius of the outer circle of the friction plate, and R i is the radius of the inner circle of the friction plate. T L (t) is the load torque applied on the output shaft of the driveline.…”
Section: A Mathematical Model Of a Two-speed Transmission System In H...mentioning
confidence: 99%
“…Li5 studied the meshing characteristics of planetary gear train when the position of the planetary frame changes under variable loads. Wang6 established a torsional dynamics model of planetary gear transmission system considering friction, time-varying meshing stiffness, meshing damping and clearance, solved the system vibration equation by Runge-Kutta method, and analyzed the bifurcation and chaos characteristics of the system through bifurcation diagrams and phase diagrams. Luo 7 established a dynamic model including time-varying meshing stiffness, sliding friction and torque, and studied the influence of sliding friction on the dynamic characteristics of planetary gear mechanisms.…”
mentioning
confidence: 99%
“…The dynamic behaviors were investigated in different system parameters. Wang et al [5] established the planetary gear transmission system considering the coupling effects of multiple nonlinear factors. The Runge-Kutta numerical method is used to solve the system vibration equation.…”
Section: Introductionmentioning
confidence: 99%
“…39 Luo et al 40 established a planetary gear set dynamic model with spalling defects and sliding friction, and found that spalling defects and sliding friction have a significant effect on the dynamic response of the planetary gear set, and finally verified the dynamic model through experiments. Wang et al 41 established a torsional dynamic model considering friction and squeeze oil film. The dynamic response of the system is obtained by a numerical solution, and the influence of lubricating oil viscosity, sun-planet backlash and ring-planet backlash on the system was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic response of the system is obtained by a numerical solution, and the influence of lubricating oil viscosity, sun-planet backlash and ring-planet backlash on the system was studied. 41 Wang and Zhu 42 established a dynamic model of the spur planetary gear-rotor-bearing of the geared turbofan (GTF) gearbox, and analyzed the dynamic response of the star bearing under different friction coefficients using a three-dimensional frequency spectrum, and finally found that the star-bearing stiffness frequency experiences surge under an increasing frictional coefficient.…”
Section: Introductionmentioning
confidence: 99%